Value of dynamic phase and SPECT/CT during Parathyroid imaging of primary hyperparathyroidism: impact on reporting and radiation exposure - Muambadzi, Ntangadzeni (My University, 2017)
Introduction: The preferred nuclear medicine method for parathyroid imaging is a nuclear medicine scan using 99mTc-sestamibi (Tc-99m MIBI). Nuclear medicine imaging using Tc-99m MIBI is the most sensitive modality. Scintigraphy using Tc-99m MIBI is also cost-effective and scintigraphy using Tc-99m MIBI for localization of hyper functioning parathyroid tissue prior to operation is the current method of choice. There are few similarities between the different methods for Tc-99m MIBI parathyroid scintigraphy and there has not been much evidence to support one over the other. However up to date there is no study in literature suggesting the use of dynamic images in parathyroid imaging. Some studies have pointed out that SPECT is more superior as compared to doing planar imaging alone without a SPECT. To improve parathyroid lesion localization, at times an addition of CT to SPECT (known as hybrid SPECT/CT) is done. However in our institution every patient has a CT component added to their SPECT. In our institution: Injection of the radiotracer is performed intravenously, dynamic/flow and static planar images of the neck are obtained at 20 minutes and 3 hours post injection. Further imaging with use of hybrid SPECT/CT is done in all our patients, to improve preoperative parathyroid glands localization. There have been very few investigations assessing the value of combining SPECT with CT, and in most studies adding a CT is only recommended for a selected population and not all patients. The number of subjects studied with hybrid SPECT/CT has been few and results have been inconclusive at most studies. Aims and objectives: This investigation compares the imaging technique we use in our institution and determines:  Whether flow/dynamic imaging adds any value to the overall results and if no value is added by dynamic can we omit the dynamic phase of the study?, this will avoid adding extra time to our studies.  The impact of fusing SPECT with CT (hybrid SPECT/CT) in all patients was also assessed and its value. If CT adds no value can we add CT component to only a selective population? example those with suspicion of ectopic parathyroid adenomas. This will minimize/reduce unnecessary technical issues, reducing length of procedure, and impact on increased costs and also radiation burden to patient. Materials and Methods: There was 273 parathyroid images reported for this study and the mean age of the patients was 57 ± 15.7 years old, 85.7% were females. All patients were suspected to have primary hyperparathyroidism with a parathyroid adenoma, patients were scanned with Tc-99m MIBI to rule out a parathyroid adenoma, at initial presentation all patients had raised serum markers (calcium and parathyroid hormone). The standard departmental imaging and reporting protocol was followed at presentation for each of the patients with flow imaging at 2sec/frame, then followed by early static at 20min and delayed static at 3 hours. In our study the reader was blinded to the patients’ final report and only the history and images of the patient were available for reporting. All sets of images that were acquired at first presentation: Flow, planar (early and delayed), SPECT and SPECT/CT were reported without seeing the final issued report. Second time around all sets of images were reported without the flow component to evaluate if we still get the same result as we did with initial reporting when we reported with the flow. Thirdly combinations of delayed planar with SPECT and delayed planar with SPECT and addition of CT (SPECT/CT) were reported without knowledge of the original report. We then identified whether adding CT component to SPECT changed the results of the overall final report that had been issued. Agreement between imaging techniques was calculated. Imaging accuracy was also measured. Results: The dynamic phase showed positive lesions in 12.5% (34) of the patients while the SPECT and CT were positive in 50.5% (138). The k-coefficient (certainty of adenoma focus) between the final report and the reader was 0.68 (95% confidence interval, 0.66–0.70). Dual phase studies that included SPECT/CT had the highest values. Statistically significantly superior to single-phase early or delayed imaging in sensitivity, area under the curve, and positive predictive value was dual-phase planar imaging, SPECT, and SPECT/CT. SPECT was statistically superior to planar static imaging. Single photon emission tomography fused with CT (SPECT/CT) in combination with any delayed imaging method was superior to dual phase planar imaging or SPECT alone for sensitivity, area under the curve, and positive predictive value. The results of the analysis imaging techniques showed a poor agreement between the dynamic phase and planar imaging (k=0.09). The measurement of agreement between the imaging techniques showed that the SPECT/CT and the SPECT alone showed a significantly very good agreement (k=0.93, p<0.001) as well as with planar. Conclusion: There was a poor agreement seen between dynamic phase and planar static imaging. The measurement of agreement between imaging techniques showed that the SPECT/CT and the SPECT alone showed a significant very good agreement. We therefore advise to eliminate the dynamic phase and only add the SPECT/CT in patients with high clinical index of suspicion for example patients with ectopic lesions or when the planar imaging is negative.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine in Nuclear Medicine Johannesburg, 2016.